OMISSION REPERCUSSIONS IN THE UTTERANCES OF ADULTS SUFFERING FROM AUTISTIC SPECTRUM DISORDER - Ulfa Kurniasih; Eli Rustinar; Azizatul Khairi (Masyarakat Linguistik Indonesia, 2023)
Autism Spectrum Disorder (hereinafter referred to as ASD ) is a developmental disorder experienced by a person since childhood, which causes an inability to communicate and express feelings. This research is an extension of previous research that investigated the language development of ASD children in relation to aspects of discourse that affect speech omission (Halliday & Matthiessen, 2013a). This study uses primary data derived from spontaneous speeches from 2 adults with ASD and 6 children with normal development. Children with normal development were included in the control group as a comparison to see the phenomenon of omission by using storytelling techniques with or without pictures. The second data collection technique is the storytelling technique without assistance. Researchers have prepared a general theme given to research participants. This study confirms and shows that the phenomenon of omission that is present in the speech of adults with ASD and children with normal development as a control group is not too much different quantitatively, but qualitatively has characteristics that can be used as comparisons. This special characteristic is related to the problem of autism spectrum disorders, namely the ability to communicate in responding to the interlocutor. In the end, the results of this study can contribute as a first step in diagnosing language disorders for people with ASD .